2004
DOI: 10.2527/2004.8251488x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supranutritional and organically bound selenium on performance, carcass characteristics, and selenium distribution in finishing beef steers1

Abstract: Dietary selenium influences the Se content in edible muscle of beef cattle. Limited data are available to describe the effects that feeds naturally high in Se have on production, carcass characteristics, and Se distribution in terminal tissues. Therefore, 43 crossbred steers (BW = 351 +/- 24 kg) were stratified by BW and assigned to one of four dietary treatments: Se adequate (CON; n = 12), Se provided as high-Se wheat (WHT; n = 9), high-Se hay (HAY; n = 11), or sodium selenate (SEO; n = 11). Daily selenium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
64
1
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 24 publications
14
64
1
14
Order By: Relevance
“…Regarding the treatments with selenium supplementation, Lawler et al (2004) supplemented selenium in cattle and found no change in fat thickness and marbling of meat, like the results of this experiment.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Regarding the treatments with selenium supplementation, Lawler et al (2004) supplemented selenium in cattle and found no change in fat thickness and marbling of meat, like the results of this experiment.…”
Section: Resultssupporting
confidence: 58%
“…Engle & Spears (2000) found no change in cooling loss or hot carcass weight with supplementation of 20 mg copper/kg of DM; however, these authors also found no reduction in fat thickness. Regarding the treatments with selenium, as the results found in present study, some authors like Lawler et al (2004) and Mahan et al (1999) supplemented selenium and found no change in hot carcass weight in cattle and swine, respectively.…”
Section: Resultsmentioning
confidence: 58%
“…Therefore, carcass must provide maximum amount of muscle, minimum of bone, and an amount of fat that varies depending on consumer preference. The proximate composition of the beef was similar between treatments and with values similar to those obtained by Lawler et al (2004), Freitas et al (2008), Razook et al (2002), Rubiano et al (2009), Souza et al (2009), and Sestari et al (2012, when working with Nelore cattle. The exception is ether extract content, which was lower, possibly due to the lower energy density of the diets used in this study compared with the aforementioned authors, who aimed at higher weight gain.…”
Section: Discussionsupporting
confidence: 51%
“…Surai (2006) reported that SeMet is retained in tissue proteins to a greater extent than selenocysteine (SeCys) or Se derived from inorganic forms. A number of studies have detailed the accumulation of Se within the tissues of animals exposed to supranutritional concentrations of organic Se (Lawler et al, 2004;Taylor, 2005) but very little information is available on either the persistency of Se or the distribution of selenised amino acids within the tissues of animals following the withdrawal of diets containing high doses of organic Se. This paper aims to redress this shortfall in information and reports on the concentration of total Se and the proportion of total Se comprised as either SeMet or SeCys in post mortem tissues of lambs following the withdrawal of high-dose SY (HSY) diets.…”
Section: Introductionmentioning
confidence: 99%